KUALITAS DIET DAN HUBUNGANNYA DENGAN PENGETAHUAN GIZI, STATUS SOSIAL EKONOMI, DAN STATUS GIZI - Nurul Muslihah; Sri Winarsih; Soemardini Soemardini; AS. Zakaria; Zainudiin Zainudiin (Food and Nutrition Society of Indonesia, 2013)
The objective of study was to assess the diet quality and its relation to nutrition knowledge, body mass index (BMI), and socio economic status (SES) among adults person. The cross sectional study was conducted with 100 adults aged ≥25 years old from Kedung Kandang sub district, Malang. Dietary quality was assessed using two non-consecutive 24-h dietary recalls and semi quantitative FFQ. Nutrition knowledge questionnaire was modified from Parmenter and Wardle. The most subjects were middle SES and the BMI were normal and overweight. The average of diet quality score was 7.14±1.96 with dietary diversity score 1.93±0.43; micronutrient adequacy score 2.3±1.4; prevention NCD score 2.87±0.92. Nutrition knowledge score was 43.3±24.6 with dietary recommendation 9.3±3.6; sources of nutrients 14±11.5; choosing foods 6.3±4.9; diet-disease relationships 13.7±8.6. Nutrition knowledge score was no correlation with BMI, dietary diversity, prevention NCD score, but positively associated with SES, quality diet, micronutrient adequacy score. SES was no associated with BMI and quality diet index. Dietary diversity score was associated with BMI. Diet quality score was associated with nutrition knowledge but no correlation with BMI and SES. The conclusion is diet quality and nutrition knowledge was still poor and not correlated with BMI and SES, but only nutrition knowledge score.